Wittgenstein, criteria and the ineffability of consciousness - Maloney, J (2010)
The present discussion seeks to determine the scope and nature of Wittgenstein's opposition to some prominent approaches to consciousness in contemporary philosophy of mind and cognitive science. We begin with some general remarks about this opposition, and in Chapter 1 appraise some prominent contemporary exemplars: Hacker & Bennett's (2003, 2007) Wittgensteinian critiques of attempts to study and define consciousness, and Searle (2007) and Block's (2007) opposing views. Their dispute hinges on whether Wittgenstein's notion of criteria yields a prima facie opposition to the distinction between consciousness and language (the 'being'/'saying' distinction) and more generally whether his later view is opposed to the ineffability of consciousness. We will demonstrate that while Wittgenstein's notion of criteria, properly understood, does provide a prima facie case against the 'being'/'saying' distinction (Chapters 2 and 3), there is an alternative sense in which Wittgenstein's view may endorse a notion of 'ineffable consciousness' importantly similar to that endorsed by Block (2007) and others. As such, Wittgenstein's position concurs neither with attempts by Block, Searle and others to distinguish consciousness from language, nor with claims such as Hacker and Bennett's which suggest a wholesale opposition to consciousness or its ineffability.